Tahap sebutan huruf konsonan Arab dalam kalangan murid prasekolah - Nik Mohd Rahimi; Harun Baharudin; Zamri Mahamod (penerbit ukm, 2010)
The aim of this study is to evaluate the pronunciation of Arabic language consonants among preschool children. The objectives of this study are to identify the level of pronunciation of Arabic Language consonants; and to identify the fluency level of Arabic consonants. This study was carried out at five preschool centers and the samples consist of 108 preschool students at the age of six. The data were collected from one set of pronunciation test based on al-Khalil Methodology. From the study, 15 consonants were found to be at the high level of fluency, 12 consonants at the moderate level, and one at the weak level.